The Effects of The New Logo on People’s Brand Awareness and Perception of Quality of Indonesia's Ministry of State-Owned Enterprises - Koentjoro , Mochammad Surjo (Journal of Marketing Development and Competitiveness, 2021)
In July 2020 Indonesia’s Ministry of State-Owned Enterprises launched a new logo aimed to reflect the country’s identity and the institution’s spirit of innovation, and collaboration. This research investigates whether the logo affects the Brand Awareness and Perception of Quality of the Ministry among Indonesians. Two groups of respondents were formed, the Experimental and the Control Group. They were given questionnaire using a six-point Likert scale. The Experimental Group were shown and asked about the new logo and the Ministry itself in terms of Nationalism, Innovation, and Cooperation. The Control Group were asked just the question about the Ministry in relation to those criteria without being shown nor asked about the new logo. Both groups' answers were then analyzed and compared, and the results from the Experimental Group were also analyzed using Linear Regression to determine the influence of the new logo on the people’s opinion about the ministry. The results show that the people from the Experimental Group consistently gave higher scores in answers to questions about the Ministry.